Investigating the contribution of laboratory parameters on plasma neurofilament light chain levels in multiple sclerosis - Nicolella, Valerio; Gelzo, Monica; Polito, Carmela; Affinito, Giuseppina; Bagnasco, Sveva; Addesso, Raffaella; Cernera, Gustavo; Sirica, Rosa; La Civita, Evelina; Fiorenza, Mariano; Novarella, Federica; Palladino, Raffaele; et al. (Frontiers in Neurology, 2025)
ObjectiveTo investigate the associations between several laboratory parameters and plasma neurofilament light chain (pNfL) in individuals with multiple sclerosis (MS), as well as their additional contribution to the established relationships between pNfL, demographics, and MS disability.MethodsIn this cross-sectional study, we included 638 people with MS (PwMS) and evaluated pNfL (using fully automated chemiluminescent enzyme immunoassay), along with demographic, clinical and laboratory variables. Laboratory variables were preliminary selected using univariate linear regression models and multicollinearity analysis. A multivariate linear regression model was then employed to determine independent predictors of pNfL levels. Finally, we used linear regression models to explore the clinical utility of adjusting pNfL level.ResultsOn the multivariate linear regression model, higher pNfL was associated with older age (Coeff = 0.15; 95%CI = 0.04, 0.26; p = 0.007), presence of cardiovascular comorbidity (Coeff = 3.67; 95%CI = 0.82, 6.51; p = 0.012), higher alkaline phosphatase (ALP) (Coeff = 0.05; 95%CI = 0.01, 0.09; p = 0.19), higher lymphocytes’ fraction (Coeff = 0.20; 95%CI = 0.08,0.33; p = 0.001), lower blood proteins (Coeff = −4.02; 95%CI = -6.09, −1.96; p < 0.001), and lower hemoglobin (HB) (Coeff = −1.01; 95%CI = −1.73, −0.27; p = 0.007). We confirmed known association between higher pNfL and worse MS-related disability (Coeff = 2.23; 95%CI = 1.58, 2.87; <0.001), which did not significantly change after including selected laboratory variables (Coeff = 1.48; 95%CI = 0.72, 2.24; p < 0.001).ConclusionAlthough laboratory markers of lymphocyte depletion and metabolic/nutritional status are correlated with pNfL levels, they do not modify its relationship with MS disability.